Effect of maternal education and encouragement on newborn care utilization: a health system intervention - Ali-Asghar Kolahi; Mohsen Abbasi-Kangevari; Alireza Abadi (BMC, 2021)
Abstract Background The objective of this health system interventional study was to determine the effect of delivering newborn-care-oriented education and encouragement on newborn care utilization. Methods This study was performed in the urban health centers of the catchment area of Tehran Defined Population, which covered 10 of the 22 municipality districts of Tehran. The two catchment areas included 10,000 families in the intervention and 20,000 families in the control areas. As many as 4837 newborns (intervention = 1544, control = 3293) were enrolled and followed until the end of the second month of life. The utilization of the three newborn care visits, as recommended by national guidelines, was compared among the intervention and control groups. Results As many as 877 (56.8%) newborns in the intervention group and 1214 (36.9%) in the control group received all their three newborn care visits. The mean number of newborn care visits was higher in the intervention group compared to the control group: 2.26 (0.99) versus 1.84 (1.07), p < 0.001. The number of newborns who did not attend any of their three newborn care visits was 143 (9.3%) in the intervention group and 468 (14.2%) in the control group. Conclusions The intervention improved newborn care utilization during the first 2 months after birth. It could be suggested that active follow-up be added to newborn care guidelines. Parents need to be informed of the necessity and benefits of newborn care and be encouraged to perform all three newborn care visits.